The effect of factors of the socio-geographic structure of mountain farms on succession on these farms - Kerbler – Kefo, Boštjan (Journal for Geography, 2009)
The basic premise of this paper is that certain factors of the socio-geographic structure of mountain farms have an influence upon succession on these farms. The conducted survey confirmed this hypothesis. The most prominent influence that was observed included factors that reflect the tradition and the opinions of the householders, and especially that express the economic power of a farm. In the conclusion of this paper, we offer some solutions regarding the problem of succession in Slovene mountain farms. These solutions are not simple, due to the complex mixed rate of influence with respect to the various factors.
Keywords: social geography; agrarian geography; rural geography; mountain farms; farm succession; Slovenia